A wideband magnetic field probe with particular emphasis on low frequency characteristics. - Frikha, Mondher. (University of Ottawa (Canada), 1991)
Measurement of transients of ambient power-line frequency magnetic fields is becoming increasingly important because of the possibility that exposure to such fields may produce effects to communication systems and various electronic devices as well as human health. Many studies have been concerned with magnetic field measurements over a wide frequency range but small attention has been paid to the measurement of transient fields. The objective of this study is to investigate the feasibility of developing a magnetic field probe operating in a broad frequency range, including the power line frequency (60 Hz), which would also be suitable for measurements of transient fields (their magnitude and phase). The sensor was modeled, simulated using computer simulation and finally designed. Its performance was tested in time and frequency domains. The sensor, which provides constant amplitude and phase response from 30 Hz to around 5 MHz for the magnetic field, has a minimal response to the electric field (30 dB or less), a sensitivity of 0.48 V/A $m\sp{-1}$ and wide dynamic range (greater than 40 dB).
Keywords: Engineering, Electronics and Electrical.